MAIS UMA STIPHRA DO BRASIL (ð˜–ð˜³ð˜µð˜©ð˜°ð˜±ð˜µð˜¦ð˜³ð˜¢-ð˜—ð˜³ð˜°ð˜´ð˜¤ð˜°ð˜±ð˜ªð˜ªð˜¥ð˜¢ð˜¦) - Piza Junior, Salvador de Toledo (REVISTA DE AGRICULTURA, 2020)
MAIS UMA STIPHRA DO BRASIL (ð˜–ð˜³ð˜µð˜©ð˜°ð˜±ð˜µð˜¦ð˜³ð˜¢-ð˜—ð˜³ð˜°ð˜´ð˜¤ð˜°ð˜±ð˜ªð˜ªð˜¥ð˜¢ð˜¦)